Avaliação multimodal de imagem na Sífilis Ocular - Sarah Pereira de Freitas Cenachi (2020)
Introduction: Syphilis remains as an important cause of uveitis. Despite the efforts to eradicate the disease, incidence rate has increased. This work has the objective to employ multimodal imaging (MI) for characterization of involvement of the posterior segment of the eye, enhanced by indocyanine green angiography(ICGA). The pathophysiology of syphilitic uveitis (SU) is thought to involve choroidal inflammation and the indocyanine green angiography (ICGA) adds to MI the perspective of more accurate study of the choroid, but has not been systematically investigated in the setting of multimodal imaging of SU. Methods: A prospective non-comparative interventional study of patients with diagnosis of syphilitic uveitis, admitted for treatment at Hospital São Geraldo between 2018 and 2019, encompassing 24 patients. Eight patients admitted between 2015 and 2017 who met the study criteria were also included. The final sample included 32 patients. They were submitted to autofluorescence (FAF), fluorescein angiography (FA), indocyanine green angiography (ICGA) and spectral domain coherence tomography (SD OCT) upon hospital admission and discharge, as well as at a follow-up visit. Demographic, laboratory, clinical and eye examination data were also analyzed. Results: Patient age ranged from 19 to 68 years-old, with a median of 45 years. Visual acuity (VA) ranged from 20/20 to hand motion, with a median of 20/40. MI revealed subclinical changes in 5 eyes of 5 patients. In the study of anatomical location of intraocular inflammation, MI detected previously unrecognized posterior involvement in 11 eyes, improving the accuracy of the anatomical classification of uveitis by 19% (11/57). On MI, geographical choroidal hypocyanescences were detected in 47% (27/58) eyes, dark spots in 72% (33/46) and a punctiform form of hypocyanescence was identified in 93% (52/56) of the eyes. On FA, 3 forms of fluorescein leakage were identified in the central retina: the classic placoid form, a form named semiplacoid, with some insinuation of a geographical area, and a third form, here named punctiform, in which speckled distribution of the contrast occurred. On OCT, changes in the external retina were very prevalent, with a multinodular hyperreflectivity in the RPE present in 78% (46/59) of the eyes, interruptions in the ellipsoid zone in 86% (51/59) and interruptions in the external limiting membrane (ELM) in 72% (42/58). Predictive factors of increased inflammation at hospital admission were found, including RPE multinodular hyperreflectivity and interruptions in ELM on OCT. Factors at hospital admission that were predictive of worse outcome at the end of treatment included VA≤ 20/200 and ELM interruptions on OCT. Conclusion: MI suggested the choroid as primary site of intraocular involvement in syphilis, with high prevalence of hypocyanescence indicating choroidal inflammatory infiltration. OCT identified extension of the disease to the retina, detailing changes in the outer layers. FA allowed recognition of forms of presentation other than the classic placoid form, namely semiplacoid and punctiform forms. MI was superior to ophthalmological exam for identification and determination of location of intraocular inflammation. Finally, MI contributed to a better understanding of syphilitic uveitis, having identified findings predictive of more severe inflammation at presentation, as well as factors of worse prognosis at the end of treatment.